Analysis of Students Mathematical Argumentation Abilities in Solving System of Linear Equation in Two Variables Problems Based on The Level of Creative Thinking - Isti Hari Wahyuni; Wiwin Sri Hidayati; Lia Budi Tristanti (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
The research is important to conduct because students’ mathematical argumentation skills are still often underdeveloped, especially when they are required to justify solutions and connect them with their level of creative thinking. Strengthening these skills is essential not only for obtaining correct answers but also for fostering logical reasoning, critical thinking, and deeper conceptual understanding in mathematics learning. The mathematical argumentation ability of junior high school students in solving SPLDV problems based on the level of creative thinking is defined as the ability of students to convey reasons (data, claims, warrants, backing, and qualifiers) to support or refute a claim derived from a solution to an SPLDV problem. The purpose of this study was to describe students’ mathematical argumentation abilities across four categories of creative thinking: very creative, creative, quite creative, and less creative in solving SPLDV problems. This study employed a qualitative descriptive approach. Data validity was ensured through time triangulation. Data analysis was conducted through data reduction, data presentation, and drawing conclusions. The results showed that students with quite creative and less creative levels were able to write data and claims and also convey them verbally, while students with very creative and creative levels tended to convey data and claims verbally. Students with very creative thinking generated warrants based on ticket prices, whereas those with creative, quite creative, and less creative thinking generated warrants based on the grouping of travel participants. All students were able to convey backing, conclusions, and qualifiers verbally.